A study of the chemical composition of oil of the azedarach seeds by using gas chromatography (GC/MS) and the definition of its properties - غالية, سهير; ابراهيم عزيز صقر,; أحمد قره علي , (Latakia University Journal -Biological Sciences Series, 2023)
The seeds of Melia azedarach L., which were collected from areas in Lattakia, were studied, and a number of compounds were identified in their oil. A mixture of (53) compounds were detected in the oil of the azedarach seeds. To find out the components and their percentage in the dry seed oil of the azedarach and determine the proportions, gas chromatography GC/MS was used. The results showed that the existing compounds follow multiple functional groups, including: hydrocarbons, phenols, alcohols, sterols, fatty acids and esters,..... It was proven that the highest percentage of hydrocarbons was recorded, reaching (34.87%), followed by fatty acids with a percentage of (27.3%), then sterols (10.74%), and phenols (2.23%). Based on previous studies that talked about the biological efficacy of many of the compounds present in the oil of the seeds of azedarach, including (antibiotics for various pests, antioxidants ... etc.), the importance of the azedarach products was shown in the health (pharmaceutical industry) and agricultural (finding anti-pests from origin natural plant). The study was carried out in the year (2022) in the laboratories of the Higher Institute for Marine Research and the Plant Protection Department, in the Faculty of Agriculture, Tishreen University.